Life before birth the moral and legal status of embryos and fetuses - Steinbock, Bonnie (New York ; Oxford : Oxford University Press, 2011)
This title provides a coherent framework for addressing bioethical issues connected to the moral status of embryos and fetuses. The book explores the conceptual and practical difficulties raised by abortion, prenatal torts, wrongful life the crime of feticide, substance abuse by pregnant women, and much more.
Previous ed.: 1992.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Fetus -- Legal status, laws, etc; Abortion -- Law and legislation; Abortion -- Moral and ethical aspects; Fetus -- Research -- Moral and ethical aspects; Prenatal care -- Moral and ethical aspects; Prenatal care -- Law and legislation